2015
DOI: 10.1038/modpathol.2014.88
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of Fédération Nationale des Centres de Lutte Contre le Cancer grade and MDM2 amplification levels in dedifferentiated liposarcoma: a study of 50 cases

Abstract: Dedifferentiated liposarcoma represents a form of liposarcoma composed of a non-lipogenic sarcoma associated with well-differentiated liposarcoma. The prognostic significance of histological grading of the dedifferentiated component remains to be elucidated due to vague grading criteria employed in previous studies. Molecular markers of tumor behavior, including amplification levels of murine double minute-2 (MDM2) and cyclindependent kinase-4 (CDK4) genes, have been explored in a limited number of cases. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 19 publications
2
38
0
Order By: Relevance
“…However, the follow‐up periods of this study might not be long enough to assess true life outcomes. High histological grade and a retroperitoneal tumour location have been reported repeatedly to be associated with worse outcomes in DDLPS . In our study, histological grade was the most important prognostic factor, while retroperitoneal tumour location was related only to shorter LRFS.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, the follow‐up periods of this study might not be long enough to assess true life outcomes. High histological grade and a retroperitoneal tumour location have been reported repeatedly to be associated with worse outcomes in DDLPS . In our study, histological grade was the most important prognostic factor, while retroperitoneal tumour location was related only to shorter LRFS.…”
Section: Discussionsupporting
confidence: 57%
“…Histological examinations were performed using specimens taken by tumour resection, except for two ossified cases whose resection specimens were unavailable. Histological tumour grading was performed only in the cases without antecedent chemotherapy or radiotherapy, using a modified French Fédération Nationale des Centers de Lutte Contre le Cancer (FNCLCC) histological grading system in which the tumour differentiation score of the FNCLCC system was replaced by a tumour atypia score …”
Section: Methodsmentioning
confidence: 99%
“…ANXA2 staining score was the product of the intensity and percentage scores. The cutoff point for a statistically significant ANXA2 expression score in terms of survival was set using the X-tile software program and defined as follows: negative (−): (0-4), weakly positive (+): (4-6), moderately positive (++): (6-9), and strongly positive (9)(10)(11)(12). The staining in HCC and benign liver diseases tissues was scored independently by the two individuals who were blinded to each other's findings and the clinical characteristics of these sections (left panel, ×40, bar 500 μm; right panel, ×400, bar 50 μm) (χ 2 =46.305, P<0.001), single tumor node (χ 2 =7.707, P= 0.005), and early TNM stage (χ 2 =44.188, P<0.001), without intrahepatic metastasis (χ 2 =8.534, P=0.003) and portal vein tumor thrombus (χ 2 =19.988, P<0.001) had a significantly better prognosis (Fig.…”
Section: Univariate and Multivariate Analyses Of Prognostic Variablesmentioning
confidence: 99%
“…Therefore, the early diagnosis is the only hope for curative therapies before metastasis of HCC is finally conquered [5], but the most important thing is to effectively screen out high-risk population for HCC according to prognostic factor [6]. With the increasing understanding of tumor biology of HCC, many new prognostic biomarkers of HCC [7,8] have been successively identified by clinical and/or pathological staging systems [9,10]. The identification of these genetic and epigenetic abnormalities in HCC Haijian Zhang and Min Yao contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the prognostic relevance of MDM2/CDK4 amplification in liposarcoma, a higher level of amplification seems to be associated with worse prognosis but has been reported not to be a statistically significant prognostic factor. 4,5 According to the previous CGH study, Forus et al reported that gain of chromosome 1q showed relation to metastasis. 2 We think that there is not a single strong predictive biomarker of clinical outcome in dedifferentiated liposarcoma.…”
mentioning
confidence: 95%